Coordinación automática de protecciones de sobrecorriente para un sistema de distribución ante desastres naturales - Caviedes Correa, Sebastián Andreé (2018)
The present research is carried out to determine the automatic coordination of Inverse Definite Minimum Time Overcurrent relays for distribution networks. The proposed algorithms are developed in MATLAB and PowerFactory, which are focused to avoid the total disconnection of customers to the main grid, improving resilience and the recovery capacity of the distribution system during disturbances. The initial study case contemplates a preliminary protection coordination in PowerFactory for a distribution network, which is affected by an external event, producing an aleatory change into topology grid due to loss of the electrical components in the distribution network. Consequently, based on short circuit analysis is possible to calculate automatically the current setting values (Pickup current) and time dial or Time Multiplier Setting (TMS) for each relay. The aforementioned procedure ensures that system maintain continuity of service in no-affected zones, preventing the total outage of distribution system as a result of absence of coordination of protection or by improper coordination of protections.